FPGAs memory synchronization and performance evaluation using the open computing language framework - Almomany, Abedalmuhdi; Jarrah, Amin (Institute of Advanced Engineering and Science, 2024)
One advantage of the open computing language (OpenCL) software framework is its ability to run on different architectures. Field programmable gate arrays (FPGAs) are a high-speed computing architecture used for computation acceleration. This work develops a set of eight benchmarks (memory synchronization functions, explained in this study) using an OpenCL framework to study the effect of memory access time on overall performance when targeting the general FPGA computing platform. The results indicate the best synchronization mechanism to be adopted to synthesize the proposed design on the FPGA computation architecture. The proposed research results also demonstrate the effectiveness of using a task-parallel model approach to avoid using high-cost synchronization mechanisms within proposed designs that are constructed on the general FPGA computation platform.